2010
DOI: 10.1007/s10198-010-0235-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the validity of the vignette approach to correct for heterogeneity in reporting health system responsiveness

Abstract: Despite the growing popularity of the vignette methodology to deal with self-reported, categorical data, the formal evaluation of the validity of this methodology is still a topic of research. Some critical assumptions need to hold in order for this method to be valid. In this paper we analyse the assumption of "vignette equivalence" using data on health system responsiveness contained within the World Health Survey. We perform several tests to check the assumption of vignette equivalence. First, we use a test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 27 publications
0
44
0
Order By: Relevance
“…In order to be able to do that, comparability of the measures used is an obvious necessary condition. This paper illustrates that correcting income satisfaction 11 A third type of tests of vignette equivalence in Rice et al (2011) uses country groupings. We cannot perform these tests since we only have two countries.…”
Section: Discussionmentioning
confidence: 99%
“…In order to be able to do that, comparability of the measures used is an obvious necessary condition. This paper illustrates that correcting income satisfaction 11 A third type of tests of vignette equivalence in Rice et al (2011) uses country groupings. We cannot perform these tests since we only have two countries.…”
Section: Discussionmentioning
confidence: 99%
“…Another concern might be the use of vignettes to search for evidence of stereotyping in decision-making, although several studies have shown vignettes to be accurate in reflecting actual clinical practice. [39][40][41][42][43] The survey response rate among students at participating schools (40.2 %) is low enough that some might question the validity of the sample. Although our data show relatively few differences among survey respondents and the larger population of senior medical students as depicted by the AAMC survey, suggesting sample validity, it is possible that non-participants and students from non-participating schools may demonstrate different decision-making tendencies than those reflected in these data.…”
Section: Discussionmentioning
confidence: 99%
“…1. Previous studies of the ranking of these vignettes across all eight domains have demonstrated their validity in relation to distinguishing between different levels of service standards (from best state to worst state), as measured by high inter-individual Spearman's rank ordered coefficients (Rice et al, 2011(Rice et al, , 2009). This implies that respondents understood the vignettes in the same way, and hence the data did not violate the essential 'vignette equivalence' assumption.…”
Section: Dependent Variable: Responsiveness Domain Scalementioning
confidence: 98%
“…The WHS vignettes have been successfully tested for eliciting a common understanding across respondents (vignette equivalence) (Rice et al, 2011;Rice et al, 2012). The data have been used to publish papers quite widely (King et al, 2013;Szwarcwald et al, 2010), which include studies on their psychometric properties (Valentine et al, 2010).…”
Section: Introductionmentioning
confidence: 99%